Analisis Keterampilan Berpikir Tingkat Tinggi Siswa SMA pada Pembelajaran Fisika - Nur Akhiralimi; Anisa Fitriani; Indah Permata Sari; Rifaatul Maulidah (JURNAL EKSAKTA PENDIDIKAN (JEP), 2022)
Higher-order thinking skills are the ability of students to work on and complete knowledge or ideas in the form of new solutions and relate them to what they find themselves. Higher-order thinking skills need to be possessed by all students so that they can solve problems in everyday life. This study aims to describe the high-level thinking skills of high school students in learning physics. This research is qualitative research with a literature study method, and the data analysis technique used is content analysis. The secondary data sources used are articles or journals from research on higher-order thinking skills, totaling ten articles or journals published in 2016 - 2021. The analysis that has been carried out has classified higher-order thinking skills based on physics subject materials, regional distribution, and grade levels which are reviewed according to the following indicators C4 (analyze), C5 (evaluate), and C6 (create or create). The data categorization results show that the average percentage of higher-order thinking skills is still in the low category in each indicator. The conclusions of this study are expected to provide information related to the description of students' higher-order thinking skills in learning physics in high school grades.